Artificial solid electrolyte interfacial film based on MXene quantum dots and preparation method and application thereof
Through an artificial solid electrolyte interface film based on MXene quantum dots, the negative electrode volume expansion and SEI film rupture of lithium battery caused by lithium dendrites is solved, and the safety and cycle life of the battery are improved.
Patent Information
- Application Number
- CN202411703445.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The growth of lithium dendrites during lithium metal charging and discharging leads to the breaking of the negative electrode solidification interface, the increase in the contact area between the lithium electrode and the electrolyte, the short circuit inside the battery and safety hazards.
Using an artificial solid electrolyte interface film based on MXene quantum dots, an aqueous MXene quantum dot solution was obtained by etching MAX phase materials, washing, hydrothermal reaction or sonication, and then mixed with the binder and coated to form a stable interface film.
The growth of lithium dendrites is effectively controlled, and the volume expansion and SEI film rupture of the lithium negative electrode during the circulation process is solved, which improves the safety of the battery and extends the circulation service life.
Smart Images

Figure CN119542362A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrochemical technology, and specifically relates to an artificial solid electrolyte interface film based on MXene quantum dots, and a preparation method and application thereof. Background Art
[0002] Lithium metal has a high theoretical specific capacity (3860 mAh g -1 ) and the lowest standard electrode potential (-3.04Vvs.SHE), it is considered to be one of the most promising next-generation high-energy density battery negative electrodes. However, during the charging and discharging process of lithium metal, the uneven lithium deposition / stripping process will lead to the formation of a large number of lithium dendrites on the negative electrode solidification interface. The formation of lithium dendrites will not only increase the contact area between the lithium electrode and the electrolyte, accelerate the consumption of the electrolyte, but also form a large amount of "dead lithium" that cannot be reused, causing the passivation of the negative electrode interface. What is more serious is that when the lithium dendrites grow to a certain extent, the sharp dendritic dendrites can pierce the diaphragm to make the two electrodes contact, causing a short circuit inside the battery, causing battery failure or causing safety hazards.
[0003] In order to solve the problem of lithium dendrite growth, many solutions have been reported, including uniform pore structure diaphragm design, three-dimensional current collector construction, functional electrolyte additives and artificial SEI membrane design. Although the above solutions have made some progress in inhibiting lithium dendrite growth, solving the above problems with simple and effective methods still faces severe challenges.
[0004] The intrinsic SEI film (artificial solid electrolyte interface film) generated by traditional electrochemistry has the problems of low mechanical strength and poor flexibility, which leads to the breakage of the SEI film during repeated charge and discharge. Compared with the intrinsic SEI film, the construction of the artificial SEI film has the great advantages of optional protective layer components and controllable reaction conditions. Therefore, the construction of the artificial SEI film has great potential in the practical application of lithium metal batteries. However, the artificial SEI film constructed with common inorganic materials still cannot solve the problem of SEI film breakage well, and will eventually lead to the expansion of the negative electrode volume. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide an artificial solid electrolyte interface membrane based on MXene quantum dots, and a preparation method and application thereof. The present invention uses MXene quantum dots as raw materials, mixes with a binder and a solvent, and then obtains an artificial solid electrolyte interface membrane by coating. The artificial solid electrolyte interface membrane obtained by the method of the present invention effectively controls the growth of lithium dendrites in secondary batteries, solves the volume expansion of lithium negative electrodes during the cycle process and the SEI membrane breakage problem, improves the safety of secondary batteries, and prolongs the cycle life of secondary batteries.
[0006] The present invention is achieved through the following technical solutions:
[0007] The method for preparing an artificial solid electrolyte interface film based on MXene quantum dots comprises the following steps:
[0008] Etching the MAX phase material and then washing it with water until it is neutral to obtain MXene nanosheets;
[0009] Dissolving MXene nanosheets in water to obtain a MXene nanosheet aqueous solution, adjusting the pH of the MXene nanosheet aqueous solution to 9.0-10.0, and then performing a hydrothermal reaction to obtain a MXene quantum dot aqueous solution;
[0010] or,
[0011] Ultrasonic treatment of MXene nanosheet aqueous solution to obtain MXene quantum dot aqueous solution;
[0012] After dispersing MXene quantum dots and a binder in a solvent to obtain a slurry, the slurry is coated and the solvent is evaporated to obtain an artificial solid electrolyte interface film based on MXene quantum dots. The present invention uses MXene quantum dots as raw materials to obtain an artificial solid electrolyte interface film.
[0013] Preferably, the amount of MXene nanosheets in the MXene nanosheet aqueous solution is 0.16 mg / mL-1.6 mg / mL.
[0014] Preferably, the etching solution is 6 mol / L concentrated hydrochloric acid, and the etching is performed at 35° C. for 24 hours.
[0015] Preferably, the pH of the MXene nanosheet aqueous solution is adjusted using ammonia water.
[0016] Preferably, the MAX phase material is selected from Ti 3 C 2 T x 、Ti 2 CT x 、V 2 CT x 、Mo 2 CT x , Nb 2 CT x One of them.
[0017] Preferably, the hydrothermal reaction conditions are: hydrothermal reaction at 100-110° C. for 6 h.
[0018] Preferably, the ultrasonic treatment time is 72-150 h, until the MXene nanosheets are broken into MXene quantum dots.
[0019] Preferably, the mass ratio of MXene quantum dots to binder is 1:9-9:1, and the binder only plays a bonding role, so the amount of binder is sufficient to achieve film formation of MXene quantum dots.
[0020] Preferably, the binder is selected from at least one of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), sodium alginate (SA), polymethyl methacrylate (PMMA), sodium carboxymethyl cellulose (CMC) or styrene-butadiene latex (also known as polystyrene butadiene copolymer) (SBR). Further, the binder is selected from polyacrylic acid (PAA) or polyvinylidene fluoride (PVDF).
[0021] Preferably, the solvent is at least one selected from tetrahydrofuran (THF), N-methylpyrrolidone (NMP), 1,4-dioxane (DOL), and ethylene glycol dimethyl ether (DME).
[0022] The present invention also protects the artificial solid electrolyte interface film based on MXene quantum dots obtained by the above preparation method.
[0023] The present invention also protects the application of artificial solid electrolyte interface membrane based on MXene quantum dots in the preparation of lithium negative electrode materials.
[0024] Preferably, the application method is: coating the slurry on the surface of a lithium sheet, and evaporating the solvent to obtain a lithium negative electrode material.
[0025] Preferably, the loading amount of MXene quantum dots on the lithium sheet is 0.3-1.0 mg / cm 2 If the MXene quantum dot loading is less than 0.3 mg / cm -2 , it cannot effectively coat the surface of the lithium sheet; if the MXene quantum dot loading is greater than 1.0 mg / cm -2 , it will cause the interface film to be too thick, affecting ion transmission.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention uses MAX phase material as raw material to prepare MXene quantum dots, and then uses MXene quantum dots as raw material to obtain an artificial solid electrolyte interface membrane under the bonding effect of a binder. Compared with the prior art method for solving the growth of lithium dendrites, the present invention uses MXene quantum dots to obtain an artificial solid electrolyte interface membrane. The preparation method of the artificial solid electrolyte interface membrane is simple and solves the problems of lithium dendrite growth, volume expansion of the lithium negative electrode during the cycle, and SEI membrane breakage.
[0028] 2. In the artificial solid electrolyte interface membrane obtained by the method of the present invention, MXene quantum dots are used as raw materials for the first time. The quantized MXene material has rich terminal lithium-philic groups, while avoiding the stacking and agglomeration effects between nanosheets, so that the integrated artificial solid electrolyte interface membrane has a good regulatory effect on lithium deposition, which can not only effectively reduce the lithium nucleation overpotential and inhibit the growth of lithium dendrites, but also can well solve the problem of breakage of the artificial solid electrolyte interface membrane.
[0029] The reasons for solving the breakage of artificial solid electrolyte interface membranes are: 1. Artificial solid electrolyte interface membranes based on MXene quantum dots can effectively alleviate the expansion problem of negative electrode lithium metal, and the lithium deposition process first occurs on the artificial solid electrolyte membrane; 2. Artificial solid electrolyte interface membranes based on MXene quantum dots have super electrolyte affinity, which is conducive to the diffusion of lithium ions on the membrane surface and avoids the aggregation of lithium ions on the negative electrode surface, thereby producing a tip aggregation effect; 3. Artificial solid electrolyte interface membranes based on MXene quantum dots have good adhesion on the lithium metal surface, which greatly improves the stability of artificial solid electrolyte interface membranes.
[0030] In addition, the surface of the MXene quantum dots introduced in the present invention contains a large number of lithium-philic groups, which can act as seed sites to induce a uniform lithium deposition process, thereby effectively inhibiting the growth of lithium dendrites and improving the coulombic efficiency of lithium metal batteries.
[0031] 3. Compared with the existing intrinsic SEI film, the present invention directly mixes MXene quantum dots with a binder and then coats them. The obtained artificial solid electrolyte interface film based on MXene quantum dots has not only a stable structure under the action of the binder, but also good flexibility and high mechanical strength, thus overcoming the problems of low mechanical strength and poor flexibility of the intrinsic SEI film generated electrochemically in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a field emission high-resolution transmission electron micrograph of the MXene quantum dots of Example 1.
[0033] Figure 2 This is an optical image of the lithium negative electrode material interface obtained using the artificial solid electrolyte interface film based on MXene quantum dots in Example 1.
[0034] Figure 3 Coulombic efficiency diagram of a bare Li-Cu battery and a MQDs@Li-Cu battery assembled with lithium negative electrode materials obtained using the artificial solid electrolyte interface film based on MXene quantum dots in Example 1.
[0035] Figure 4Voltage-time diagram of a bare Li / / Li battery and a MQDs@Li / / MQDs@Li battery assembled with the lithium negative electrode material obtained using the artificial solid electrolyte interface film based on MXene quantum dots in Example 1.
[0036] Figure 5 LiFePO assembled with the lithium negative electrode material obtained by using the artificial solid electrolyte interface film based on MXene quantum dots in Example 1 4 / / Rate performance diagram of MQDs@Li battery. DETAILED DESCRIPTION
[0037] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0038] Taking into account that the artificial SEI membrane constructed with traditional inorganic materials in the prior art cannot solve the problem of SEI membrane breakage well, the present invention starts with the selection of inorganic materials and uses MXene quantum dots as the raw material of SEI membrane for the first time. After mixing and coating the MXene quantum dots with a binder, it is found that the obtained artificial solid electrolyte interface membrane not only effectively controls the growth of lithium dendrites in secondary batteries, but also solves the volume expansion of the lithium negative electrode during the cycle and the SEI membrane breakage problem.
[0039] The present invention is studied by using embodiments below, and the specific research methods and results are as follows:
[0040] Example 1
[0041] The method for preparing an artificial solid electrolyte interface film based on MXene quantum dots comprises the following steps:
[0042] (1) Etch Ti by acid etching 3 AlC 2 MAX phase powder, Ti 3 C 2 T x MXene aqueous solution with a concentration of 5 mg mL -1 .
[0043] (2) Take 8 mL of Ti 3 C 2 T xMXene aqueous solution, add 72 mL of water, then add ammonia water and adjust the pH value to 9.0, then place it in a reactor, hydrothermally react at 100°C for 6 hours, and then collect the MXene quantum dots by filtration and freeze-drying.
[0044] (3) Weigh 0.016 g of Ti from step (2) 3 C 2 T x MXene quantum dots were mixed with 0.004 g of PVDF and fully ground, dispersed in 600 μL of NMP in a glove box and ultrasonically treated for 12 h to obtain a slurry. After the slurry was coated, it was first dried at room temperature for 10 min and then dried at 60 ° C for 24 h to obtain an artificial solid electrolyte interface membrane based on MXene quantum dots.
[0045] The method for preparing a lithium negative electrode comprises the following steps:
[0046] The artificial solid electrolyte interface film based on MXene quantum dots is loaded on a 1cm 2 The surface of the lithium sheet is coated with a lithium negative electrode.
[0047] Example 2
[0048] The method for preparing an artificial solid electrolyte interface film based on MXene quantum dots comprises the following steps:
[0049] (1) Etch Ti by acid etching 3 AlC 2 MAX phase powder to obtain Ti 3 C 2 T x MXene aqueous solution with a concentration of 5 mg mL -1 .
[0050] (2) Take 8 mL of the above Ti 3 C 2 T x MXene aqueous solution, add 72 mL of water, add appropriate amount of ammonia water to adjust the pH value of the solution to 9, place the solution in a reactor at 100 ° C for 6 hours, and then collect the quantum dot samples by filtration and freeze-drying.
[0051] (3) Weigh 0.016 g of Ti obtained in step (2) 3 C 2 T xMXene quantum dots and 0.004 g of PVDF were fully ground and dispersed into a mixed solution of 300 μL of NMP and 300 μL of THF in a glove box and ultrasonically treated for 12 h to obtain a slurry. After the slurry was coated, it was first dried at room temperature for 10 min and then dried at 60 °C for 24 h to obtain an artificial solid electrolyte interface film based on MXene quantum dots.
[0052] The method for preparing a lithium negative electrode comprises the following steps:
[0053] The artificial solid electrolyte interface film based on MXene quantum dots is loaded on a 1cm 2 The surface of the lithium sheet is coated with a lithium negative electrode.
[0054] Example 3
[0055] The method for preparing an artificial solid electrolyte interface film based on MXene quantum dots comprises the following steps:
[0056] (1) Etch Ti by acid etching 3 AlC 2 MAX phase powder to obtain Ti 3 C 2 T x MXene aqueous solution with a concentration of 5 mg mL -1 .
[0057] (2) Take 8 mL of the above Ti 3 C 2 T x MXene aqueous solution, add 72 mL of water, add appropriate amount of ammonia water to adjust the pH value of the solution to 9, place the solution in a reactor at 100 ° C for 6 hours, and then collect the quantum dot samples by filtration and freeze-drying.
[0058] (3) Weigh 0.016 g of Ti obtained in step (2) 3 C 2 T x MXene quantum dots and 0.004 g of PVDF were fully ground and dispersed into a mixed solution of 300 μL of DOL and 300 μL of DME in a glove box and ultrasonically treated for 12 h to obtain a slurry. After the slurry was coated, it was first dried at room temperature for 10 min and then dried at 60 °C for 24 h to obtain an artificial solid electrolyte interface film based on MXene quantum dots.
[0059] The method for preparing a lithium negative electrode comprises the following steps:
[0060] The artificial solid electrolyte interface film based on MXene quantum dots is loaded on a 1cm 2 The surface of the lithium sheet is coated with a lithium negative electrode.
[0061] Example 4
[0062] The method for preparing an artificial solid electrolyte interface film based on MXene quantum dots comprises the following steps:
[0063] (1) Etch Ti by acid etching 3 AlC 2 MAX phase powder to obtain Ti 3 C 2 T x MXene aqueous solution with a concentration of 5 mg mL -1 .
[0064] (2) Take 8 mL of the above Ti 3 C 2 T x MXene aqueous solution, add 72 mL of water, add appropriate amount of ammonia water to adjust the pH value of the solution to 10, place the solution in a reactor at 110 ° C for 6 hours, and then collect the quantum dot samples by filtration and freeze-drying.
[0065] (3) Weigh 0.016 g of Ti obtained in step (2) 3 C 2 T x MXene quantum dots and 0.004 g of PVDF were fully ground and dispersed into 600 μL of NMP solution in a glove box for ultrasonic treatment for 12 h to obtain a slurry. After the slurry was coated, it was first dried at room temperature for 10 min and then dried at 60 ° C for 24 h to obtain an artificial solid electrolyte interface membrane based on MXene quantum dots.
[0066] The method for preparing a lithium negative electrode comprises the following steps:
[0067] The artificial solid electrolyte interface film based on MXene quantum dots is loaded on a 1cm 2 The surface of the lithium sheet is coated with a lithium negative electrode.
[0068] Example 5
[0069] The method for preparing an artificial solid electrolyte interface film based on MXene quantum dots comprises the following steps:
[0070] (1) Etch Ti by acid etching 3 AlC 2 MAX phase powder to obtain Ti 3 C 2 T x MXene aqueous solution with a concentration of 5 mg mL -1 .
[0071] (2) Take 8 mL of the above Ti3 C 2 T x MXene aqueous solution, to which 72 mL of water was added, was ultrasonically treated at room temperature for 72 h, and then the MXene quantum dot sample was collected by filtration and freeze-drying.
[0072] (3) Weigh 0.016 g of Ti obtained in step (2) 3 C 2 T x MXene quantum dots and 0.004 g of PVDF were fully ground and dispersed into 600 μL of NMP solution in a glove box for ultrasonic treatment for 12 h to obtain a slurry. After the slurry was coated, it was first dried at room temperature for 10 min and then dried at 60 ° C for 24 h to obtain an artificial solid electrolyte interface membrane based on MXene quantum dots.
[0073] The method for preparing a lithium negative electrode comprises the following steps:
[0074] The artificial solid electrolyte interface film based on MXene quantum dots is loaded on a 1cm 2 The surface of the lithium sheet is coated with a lithium negative electrode.
[0075] Example 6
[0076] The method for preparing an artificial solid electrolyte interface film based on MXene quantum dots comprises the following steps:
[0077] (1) Etch Ti by acid etching 3 AlC 2 MAX phase powder to obtain Ti 3 C 2 T x MXene aqueous solution with a concentration of 5 mg mL -1 .
[0078] (2) Take 8 mL of the above Ti 3 C 2 T x MXene aqueous solution, to which 72 mL of water was added, was ultrasonically treated at room temperature for 72 h, and then the MXene quantum dot sample was collected by filtration and freeze-drying.
[0079] (3) Weigh 0.016 g of Ti obtained in step (2) 3 C 2 T xMXene quantum dots and 0.004 g of PVDF were fully ground and dispersed into a mixed solution of 300 μL of NMP and 300 μL of THF in a glove box and ultrasonically treated for 12 h to obtain a slurry. After the slurry was coated, it was first dried at room temperature for 10 min and then dried at 60 °C for 24 h to obtain an artificial solid electrolyte interface film based on MXene quantum dots.
[0080] The method for preparing a lithium negative electrode comprises the following steps:
[0081] The artificial solid electrolyte interface film based on MXene quantum dots is loaded on a 1cm 2 The surface of the lithium sheet is coated with a lithium negative electrode.
[0082] Example 7
[0083] The method for preparing an artificial solid electrolyte interface film based on MXene quantum dots comprises the following steps:
[0084] (1) Etch Ti by acid etching 3 AlC 2 MAX phase powder to obtain Ti 3 C 2 T x MXene aqueous solution with a concentration of 5 mg mL -1 .
[0085] (2) Take 8 mL of the above Ti 3 C 2 T x MXene aqueous solution, to which 72 mL of water was added, was ultrasonically treated at room temperature for 72 h, and then the MXene quantum dot sample was collected by filtration and freeze-drying.
[0086] (3) Weigh 0.016 g of Ti obtained in step (2) 3 C 2 T x MXene quantum dots and 0.004 g of PVDF were fully ground and dispersed into a mixed solution of 300 μL of DOL and 300 μL of DME in a glove box and ultrasonically treated for 12 h to obtain a slurry. After the slurry was coated, it was first dried at room temperature for 10 min and then dried at 60 °C for 24 h to obtain an artificial solid electrolyte interface film based on MXene quantum dots.
[0087] The method for preparing a lithium negative electrode comprises the following steps:
[0088] The artificial solid electrolyte interface film based on MXene quantum dots is loaded on a 1cm 2 The surface of the lithium sheet is coated with a lithium negative electrode.
[0089] Example 8
[0090] The method for preparing an artificial solid electrolyte interface film based on MXene quantum dots comprises the following steps:
[0091] (1) Etch Ti by acid etching 3 AlC 2 MAX phase powder to obtain Ti 3 C 2 T x MXene aqueous solution with a concentration of 5 mg mL -1 .
[0092] (2) Take 8 mL of the above Ti 3 C 2 T x The MXene aqueous solution was prepared by adding 72 mL of water, which was ultrasonically treated at room temperature for 150 h, and then the MXene quantum dot sample was collected by filtration and freeze-drying.
[0093] (3) Weigh 0.016 g of Ti obtained in step (2) 3 C 2 T x MXene quantum dots and 0.004 g of PVDF were fully ground and dispersed into 600 μL of NMP solution in a glove box for ultrasonic treatment for 12 h to obtain a slurry. After the slurry was coated, it was first dried at room temperature for 10 min and then dried at 60 ° C for 24 h to obtain an artificial solid electrolyte interface membrane based on MXene quantum dots.
[0094] The method for preparing a lithium negative electrode comprises the following steps:
[0095] The artificial solid electrolyte interface film based on MXene quantum dots is loaded on a 1cm 2 The surface of the lithium sheet is coated with a lithium negative electrode.
[0096] In Examples 1-8 of the present invention, artificial solid electrolyte interface films based on MXene quantum dots are prepared to solve the volume expansion and SEI film breakage problems of lithium negative electrodes during the cycle process. The lithium negative electrode and the artificial solid electrolyte interface film based on MXene quantum dots of Example 1 are used as examples for research. The specific research methods and results are as follows:
[0097] Figure 1 The results show that the prepared MXene quantum dots have uniform size, and statistical results show that the average particle size of MXene quantum dots is 2.75nm.
[0098] Figure 2The results show that the surface of the lithium negative electrode material obtained by using the artificial solid electrolyte interface film based on MXene quantum dots in Example 1 is basically flat, which is beneficial to avoid the aggregation effect of lithium ions.
[0099] The lithium negative electrode material (MQDs@Li for short) obtained by the artificial solid electrolyte interface film based on MXene quantum dots in Example 1 was used to assemble MQDs@Li-Cu battery, MQDs@Li / / MQDs@Li battery and LiFePO 4 / / MQDs@Li battery, all batteries were assembled in a glove box filled with argon (water and oxygen values were both less than 0.01PPm), and standard CR2032 button cells were obtained.
[0100] The separators used in the assembled batteries are all commercial Celgard 2325 separators. 4 / / For MQDs@Li batteries, pure lithium or MQDs@Li is used as the negative electrode, and the positive electrode is prepared by mixing the active material LiFePO 4 , conductive carbon black and PVDF are mixed, then ground in N-methylpyrrolidone solution and then coated on carbon-coated aluminum foil.
[0101] For MQDs@Li / / MQDs@Li battery, pure lithium sheet is used as positive electrode and MQDs@Li is used as negative electrode.
[0102] For MQDs@Li-Cu batteries, the copper sheet is used as the positive electrode and MQDs@Li is used as the negative electrode.
[0103] Figure 3 The results show that at 0.5 mA / cm 2 At a current density of , after 150 lithium deposition / stripping behaviors, the coulombic efficiency of the MQDs@Li-Cu battery was 97.86%; on the contrary, the coulombic efficiency of the Li-Cu battery dropped seriously after 53 cycles, and then completely failed after 78 cycles.
[0104] Figure 4 The results show that the MQDs@Li / / MQDs@Li battery has a 2 The Li / / Li battery can cycle stably at a current density of 1400 h, with a final overpotential of only 19.9 mV. On the contrary, the Li / / Li battery shows a significant voltage increase after 700 h of cycling, indicating serious lithium dendrite growth inside the Li / / Li battery.
[0105] Figure 5 The results show that LiFePO 4LiFeO as cathode and MQDs@Li assembly 4 / / MQDs@Li battery showed excellent rate performance, with an initial discharge capacity of 163.05mAh / g at 0.2C and a capacity of 82.64mAh / g at 10C. When the current density returned to 0.2C, it still showed a discharge capacity of 159.23mAh / g, and a capacity retention rate of 95.12% after 150 cycles. This fully demonstrates the practicality of MQDs@Li.
[0106] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.
Claims
1. A method for preparing an artificial solid electrolyte interface film based on MXene quantum dots, characterized in that: The steps include: MXene quantum dots are prepared using MAX phase materials as raw materials; After dispersing MXene quantum dots and a binder in a solvent to obtain a slurry, the slurry is coated and the solvent is evaporated to obtain an artificial solid electrolyte interface film based on MXene quantum dots.
2. The method for preparing an artificial solid electrolyte interface film based on MXene quantum dots according to claim 1, characterized in that: The mass ratio of MXene quantum dots to binder is 1:9-9:
1.
3. The method for preparing an artificial solid electrolyte interface film based on MXene quantum dots according to claim 1, characterized in that: The binder is selected from at least one of vinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, sodium alginate, polymethyl methacrylate, sodium carboxymethyl cellulose or styrene-butadiene latex.
4. The method for preparing an artificial solid electrolyte interface film based on MXene quantum dots according to claim 1, characterized in that: The solvent is selected from at least one of tetrahydrofuran, N-methylpyrrolidone, 1,4-dioxane or ethylene glycol dimethyl ether.
5. The method for preparing an artificial solid electrolyte interface film based on MXene quantum dots according to claim 1, characterized in that: MXene quantum dots were prepared according to the following steps: Etching the MAX phase material and then washing it with water until it is neutral to obtain MXene nanosheets; The MXene nanosheets are dissolved in water to obtain a MXene nanosheet aqueous solution, the pH of the MXene nanosheet aqueous solution is adjusted to 9.0-10.0, and then a hydrothermal reaction is performed to obtain a MXene quantum dot aqueous solution, and the water is evaporated to obtain MXene quantum dots.
6. The method for preparing an artificial solid electrolyte interface film based on MXene quantum dots according to claim 1, characterized in that: MXene quantum dots were prepared according to the following steps: Etching the MAX phase material and then washing it with water until it is neutral to obtain MXene nanosheets; The MXene nanosheets are dissolved in water to obtain a MXene nanosheet aqueous solution, the MXene nanosheet aqueous solution is ultrasonically treated to obtain a MXene quantum dot aqueous solution, and the water is evaporated to obtain MXene quantum dots.
7. An artificial solid electrolyte interface film based on MXene quantum dots prepared by the preparation method according to claim 1.
8. Use of the artificial solid electrolyte interface film based on MXene quantum dots according to claim 7 in the preparation of lithium negative electrode materials.
9. The use of the artificial solid electrolyte interface film based on MXene quantum dots in the preparation of lithium negative electrode materials according to claim 8, characterized in that: The application method is: The slurry is coated on the surface of the lithium sheet, and after the solvent is evaporated, a lithium negative electrode material is obtained.
10. The use of the artificial solid electrolyte interface film based on MXene quantum dots in the preparation of lithium negative electrode materials according to claim 9, characterized in that: The loading amount of MXene quantum dots on the lithium sheet is 0.3-1.0 mg / cm 2 .
Citation Information
Cited By
Lithium-loving elastic electrolyte, preparation method thereof and solid-state lithium metal battery
CN120127213A